ANALYSIS OF PERSONALISATION OF ARTIFICIAL INTELLIGENCE, GAMIFICATION, AND VIRTUAL TRY-ON ON CUSTOMER RETENTION ON THE SHOPEE PLATFORM - wakhida, siti nur maratul; Farida, Ida (Journal of Social and Economics Research, 2025)
This study aims to examine how the combination of artificial intelligence personalisation, gamification, and virtual try-on features can optimally contribute to improving customer retention on the Shopee platform. This study uses a quantitative approach as its research method. The types of data used are primary and secondary data, with data collection using questionnaires. The population of this study consists of active users of the Shopee platform in Semarang City aged 17-40 years, who have used AI personalisation, gamification, and virtual try-on features for at least the last 6 months. The number of respondents is unknown, and the sample size is 111 respondents. The sample was determined using non-probability sampling techniques through purposive sampling. Data analysis techniques included descriptive statistical tests, instrument tests, classical assumption tests, multiple linear regression, and hypothesis testing. The results of the study showed that artificial intelligence had a positive and significant effect on customer retention, gamification had a positive and significant effect on customer retention, and virtual try-on had a positive and significant effect on customer retention.